Aplicação da metodologia scrum em uma empresa de tecnologia do Rio Grande do Norte - Pereira, Leidiane Fortaleza Ribeiro (2024)
The flexible nature of the scrum framework has supported technology teams in adapting to customer needs quickly while delivering value in agile cycles. In addition, the principles of collaboration and seeking feedback from the customer in various agile methodologies ensured that the service was provided as needed. The objective of this work is to analyze, plan, implement, and evaluate the use of the scrum methodology in managing the operation of a technology company located in Natal, Rio Grande do Norte, in order to measure the impacts on operational efficiency through indicators. For this purpose, the research was characterized as applied in nature and exploratory in objective. A combined approach was used with action research as the method of work, since a study with high interaction between the researcher and the coordinators, analysts, and developers of the company's operations sector was proposed. The research was divided into five stages: defining the context and purpose of the action research; data collection and analysis; planning of actions; implementation of actions; and evaluation of results. In the first stage, the context and purpose of the action research were presented, establishing an understanding of the company's situation by presenting its initial situation regarding scrum practices, delimiting the problems encountered, and establishing the question and objectives of the study. The second stage, where data collection and analysis were carried out, aimed to diagnose the company's situation in detail and how the collected data would be used to start planning. The third stage concerns the construction of action planning and evaluation metrics of results, showing which proposed actions were implemented to measure changes and impacts on the company's operation. The fourth stage relates to the implementation of action plans and monitoring to evaluate results. Finally, in the fifth stage, it was possible to evaluate the results achieved, concluding that the implementation of action plans resulted in a significant increase in operational efficiency.